Wayang Topeng Malangan: Sebuah Kajian Historis Sosiologis - MUSTHOFA KAMAL (Institut Seni Indonesia Yogyakarta, 2008)
Malangan Mask Dance: A Sociology History Perspective. This research represents the sociology history studyof the malangan mask puppet in Malang, East Java. Sociology history approach in this paper is used to fi nd theorigins, philosophy, distribution and function of malangan mask puppet and the form of presentation. As performanceart, mask puppet that i spread in poor areas has a close relationship with a social system that develops in itscommunity. Social system is the mechanization grown from a concept namely; a way of thinking from its society inviewing the reality of its life. Malang mask puppet presentation at the level of social function is seen as masks puppetsasked to enliven a feast. It appears that the presence of the show is a reality which is kinship and fellowship. Thereality is seen in the presence of the host, the sinoman, performance and audiences.